Severe bradycardia in a teenager as the initial manifestation for Guillain Barré syndrome: a case report - C. Bonilla; M. I. Alvarez-Olmos; C. Uribe; J. Fernández-Sarmiento (BMC, 2022)
Abstract Background Guillain-Barré syndrome is the most common cause of flaccid paralysis, with multiple known clinical variants. Autonomic dysfunction, although frequently reported in the clinical course, is often overlooked in the pediatric population and is usually not the initial presenting symptom in this age group Case presentation We present the case of a previously healthy 17-year-old who arrived at the Emergency Department complaining of gastrointestinal symptoms associated with lipothymia. An initial electrocardiogram (ECG) showed sustained sinus bradycardia subsequently associated with arterial hypertension. Structural and inflammatory cardiac pathology were ruled out, as well as auriculoventricular conduction block and posterior reversible encephalopathy syndrome. On the ninth day after initial symptoms, the patient presented sensory and motor nerve disturbances with the cerebrospinal fluid analysis showing a clear albumin-cytologic dissociation, consistent with an atypical presentation of GBS with autonomic dysfunction. Immunoglobulin therapy was administered, developing subsequent aseptic meningitis, that required discontinuation of previous therapy and treatment with plasmapheresis. Clinical improvement was achieved with full motor function recovery. Conclusion This case illustrates a Guillain-Barré syndrome variant in which autonomic dysfunction preceded neurologic deficit, a finding uncommon in children, emphasizing this as an important differential diagnosis for severe bradycardia in pediatric patients.